Sacred channels : the archaic illusion of communication - Hörl, Erich (Recursions: theories of media, materiality, and cultural techniques., 2018)
Erich Hörl's Sacred Channels is an original take on the history of communication theory and the cultural imaginary of communication understood through the notions of the sacred and the primitive. Hörl offers insight into the shared ground of anthropology and media theory in the nineteenth and twentieth centuries and presents an archeology of the philosophy of technology that underpins contemporary culture. This singular and unique project focuses on the ethnological disciplines and their phantasmatic imaginations of a prealphabetical realm of the sacred and the primitive but reads them in the context of media cultural questions as epistemic unconscious and as projections of the emerging postalphabetical condition. Drawing inspiration from work by the likes of Friedrich Kittler, Hörl's understanding of cybernetics in the post-World War II interdisciplinary field informs a rich analysis that is of interest to media scholars and to anyone seeking to understand the historical and theoretical underpinnings of the humanities in the age of technical media.